Flow theory – goal orientation theory: positive experience is related to athlete’s goal orientation - Stavrou, Nektarios A. M.; Psychountaki, Maria; Georgiadis, Emmanouil; Karteroliotis, Konstantinos; Zervas, Yannis (Frontiers in Psychology, 2015)
The main purpose of this study was to examine the relationship between flow experience and goal orientation theory, as well as, the differences in flow experience based on the orthogonal model of goal orientation theory. Two hundred and seventy eight athletes completed the Task and Ego Orientation Sport Questionnaire based on how they usually feel. The Flow State Scale was completed thirty minutes after an important competition, along with the challenge-skill ratings, based on how athletes felt during the particular competition. The results indicated that the athletes’ task orientation may be the critical factor for attaining flow in competitive sport, feeling more skillful and estimating the upcoming competition as challenging, while ego orientated athletes lack these elements, which are important for them to get into flow. Additionally, the balance between athletes’ goal orientation preferences seems important for the formation of flow experience.